Monetary Policy Shifts and the Forward Discount Puzzle (2013)
This paper argues that considerable switches in monetary policy are able to explain a major part of the forward discount puzzle. We build a theoretical model suggesting that violations of the uncovered interest rate parity are owed to shifts in monetary policy from a destabilizing (when the Taylor principle is violated) to a stabilizing regime (when a central bank follows a Taylor-type rule). Following the switch is an \adjustment period" during which forecasters gradually update their expectations, eventually restoring the parity. It is in this adjustment period, when the forward discount puzzle arises. In the second part of the paper we test the model on the Canadian dollar, German mark, and British pound, all against the US dollar. Results indicate that the forward discount puzzle loses signi cance after allowing for an adjustment period of about 1 { 2 years. Our results are robust to various di erent speci cations, such as the use of di erent maturities or base currencies. Further, it seems unlikely that our results coincide with contemporaneous events.